RESILIENSI PADA ANAK BERKONFLIK DENGAN HUKUM (ABH) DI INDONESIA DITINJAU DARI EFIKASI DIRI - Amalia, Rizka; Nuqul, Fathul Lubabin (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The recidivism rate in Indonesia in the case of ABH reached 42,8% (Marliana, 2017). Then, an effective interpolation is needed to achieve personal qualities through resilience. The purpose of this paper was to determine the effect of self-efficacy on increasing resilience on ABH in Indonesia.This paper is using a quantitative method that had 102 subjects of ABH which consist of representatives of some regions in Indonesia. The data collection used in this research is a cluster sampling technique. The data collection was used two-scale, named Resiliency Scales for Children and Adolescents (Saklofske et al, 2016) which consist of 51 items and the “General Self-Efficacy Scale” (Schwar & Jerussalem, 1995) which consist of 10 items. The result of the analysis shows that the range of resiliency on ABH is intermediate level with 52,9% of the presentation. Simultaneous results obtained by the regression analysis show that there is no significant effect between self-efficacy on law conflicted children's resilience in Indonesia.